2010
DOI: 10.1016/j.visres.2010.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Teach to reach: The effects of active vs. passive reaching experiences on action and perception

Abstract: Reaching is an important and early emerging motor skill that allows infants to interact with the physical and social world. However, few studies have considered how reaching experiences shape infants’ own motor development and their perception of actions performed by others. In the current study, two groups of infants received daily parent guided play sessions over a two-week training period. Using “Sticky Mittens”, one group was enabled to independently pick up objects whereas the other group only passively o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
228
6

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 167 publications
(241 citation statements)
references
References 50 publications
7
228
6
Order By: Relevance
“…In a more controlled version of the sticky mittens procedure, Libertus and Needham (2010) showed that active engagement and first-hand experiences with reaching are necessary to induce changes in reaching behavior or face preferences. In this experiment, one group of infants received Active Training using Velcro mittens while a second group received Passive Training providing closely matched, parent-guided visual and tactile stimulation using similar mittens and toys but without first-hand reaching experiences because 'nonsticky' mittens were used.…”
Section: Reaching Onset and Its Consequencesmentioning
confidence: 99%
See 2 more Smart Citations
“…In a more controlled version of the sticky mittens procedure, Libertus and Needham (2010) showed that active engagement and first-hand experiences with reaching are necessary to induce changes in reaching behavior or face preferences. In this experiment, one group of infants received Active Training using Velcro mittens while a second group received Passive Training providing closely matched, parent-guided visual and tactile stimulation using similar mittens and toys but without first-hand reaching experiences because 'nonsticky' mittens were used.…”
Section: Reaching Onset and Its Consequencesmentioning
confidence: 99%
“…For comparison purposes, data from an additional 36 infants who completed the PT (n = 18) or the AT (n = 18) training procedures was obtained from previously published reports (Libertus & Needham, 2010, 2011 and analyzed along with data collected for the current study. These two groups provide a critical comparison for the EE and ME procedures as the AT group experienced both parental encouragement and control over object whereas the PT group experienced neither.…”
Section: Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the initial stages of infancy, these are simple and reflexive functions that engage a limited repertoire of impulses. However, the process continues to develop, quantitatively as well as qualitatively, at all stages of development with progressive expansions in efficiency and richness, becoming activities like manipulation, experimentation, adventuring, and even leadership [148][149][150][151][152].…”
Section: Visceral Central Executive Subsystem Proactive Sensory-motormentioning
confidence: 99%
“…Research in developmental psychology and pediatric rehabilitation demonstrates that active (i.e., self-directed) movement experiences are fundamentally different and more advantageous compared to passive movement experiences (Held and Hein, 1963;Libertus and Needham, 2010;Jones et al, 2012;Lobo et al, 2013). Thus, the relatively passive lives of young children with disabilities who experience limited mobility are especially disturbing.…”
Section: Introductionmentioning
confidence: 99%